Will puberty last my whole life? : real answers to real questions from preteens about body changes, sex, and other growing-up stuff - Metzger, Julie Giesy (Sasquatch Books, 2011)
"This flip book for boys and girls between the ages of 9 and 12 has questions asked by girls in one half of the book; flip it over and questions asked by boys are on the other side. Contains honest, informative, and reassuring answers to questions pre-adolescents have about puberty, friends, feelings, sex, pimples, babies, body hair, menstruation, bras, and much more. Straightforward, age-appropriate answers to REAL questions from preteens are provided by an experienced nurse-and-physician team who have been giving popular seminars to moms and daughters, and dads and sons, in Seattle and Palo Alto for more than twenty years. Each of the questions in the book has been asked--many of them frequently!--by kids during their seminars. Filled with fun, full-color illustrations throughout"--